Energy performance design and analysis of a passive collector system applied to an Andean House - Soto Holgado, Francisco (2024)
The study presents and analyzes a housing module design with a passive collector system that collects via thermal inertia and air convection. The aim is to find an optimal response to the climatic conditions of the meso- and high-altitude Peruvian Andes regions, which are located in the city, province, and region of Cusco. The analysis and comparison of the thermal responses of the proposal and the traditional module, whose data were obtained using Design Builder, are conditioned by average temperatures below 12°C, which reach below 0°C from June to August. The results show that the project outperformed the traditional module in terms of energy performance, with average solar gains of 95 kWh/day and increased average indoor and outdoor air temperatures of 6°C and 8°C, respectively. This demonstrates that the thermal comfort of buildings can be improved by properly establishing relationships between collector surface, habitable volume, inertia, and thermal material transmittance.